2005
DOI: 10.1002/cncr.21283
|View full text |Cite
|
Sign up to set email alerts
|

The predictive value of CD8, CD4, CD68, and human leukocyte antigen‐D‐related cells in the prognosis of cutaneous malignant melanoma with vertical growth phase

Abstract: BACKGROUND. To establish the prognostic value of immune system cells that infiltrate melanoma, the authors evaluated the distribution and density of T lymphocyte subsets, macrophages, and dendritic cells in samples of primary cutaneous melanoma from 47 patients with Stage I and II melanoma according to the American Joint Committee on Cancer staging system. \ud \ud METHODS. immunohistochemical demonstrations of CD8 and CD4 lymphocytes, CD68 macrophages, human leukocyte antigen-D-related (HLA-DR) cells, S-100 pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
87
0
6

Year Published

2007
2007
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 143 publications
(104 citation statements)
references
References 75 publications
10
87
0
6
Order By: Relevance
“…Tregs may, thus, not be the main suppressor cells at the tumor site, whereas other suppressive cells may hamper antitumor immunity locally in our model. In line with such an assumption, we have recently shown that type 2 macrophages infiltrate massively the most aggressive metastases (21), which is consistent with observations in human melanoma biopsies (26)(27)(28). In contrast, the proportion of Tregs among CD4 + T cells was increased in the spleen and TdLNs of MT/ret mice without vitiligo, in agreement with the accumulation of Tregs observed in TdLNs few days after tumor cell implantation in several transplanted tumor models (7).…”
Section: Discussionsupporting
confidence: 89%
“…Tregs may, thus, not be the main suppressor cells at the tumor site, whereas other suppressive cells may hamper antitumor immunity locally in our model. In line with such an assumption, we have recently shown that type 2 macrophages infiltrate massively the most aggressive metastases (21), which is consistent with observations in human melanoma biopsies (26)(27)(28). In contrast, the proportion of Tregs among CD4 + T cells was increased in the spleen and TdLNs of MT/ret mice without vitiligo, in agreement with the accumulation of Tregs observed in TdLNs few days after tumor cell implantation in several transplanted tumor models (7).…”
Section: Discussionsupporting
confidence: 89%
“…Conversely, CD8 + T lymphocytes are potent effectors of adaptive tumor immunity through their production of IFN-γ as well as initiation of perforin/granzyme or Fas ligand-dependent cytolysis following TCRmediated engagement by tumor antigens (3,4). The presence of CD8 + T cells in ovarian, colorectal, and melanoma patient tumors is correlated with improved survival and can be a better prognostic indicator than conventional tumor staging (5)(6)(7).…”
Section: Introductionmentioning
confidence: 99%
“…14,33,62 Unlike in other tumor types, 24,33,37,41 a prognostic role of macrophage infiltration was not confirmed in cutaneous melanoma. 50 Beside macrophages, T lymphocytes are often major components of tumor infiltrates in many solid tumors, and their central role in antitumor immunity is well established. However, tumor-infiltrating T cells have been shown to be functionally defective, incompletely activated or anergic.…”
Section: Introductionmentioning
confidence: 99%